Differences in Neonatal Outcomes Among Premature Infants Exposed to Mother's Own Milk Versus Donor Human Milk. (1st December 2022) - Cartagena, Diana; Penny, Frances; McGrath, Jacqueline M.; Reyna, Barbara; Parker, Leslie A.; McInnis, Joleen
Abstract : Background: Growing evidence supports the superior benefits of exposure to mother's own milk (MOM) in reducing prematurity-related comorbidities. Neonatal exposure to donor human Milk (DHM) is a suitable alternative when MOM is insufficient or unavailable. However, the same protective composition and bioactivity in MOM are not present in DHM. Additional evidence is needed to justify and inform evidence-based practices increasing MOM provision while optimizing adequate use of DHM for premature infants. Purpose: A systematic review of the literature was conducted to determine differences in neonatal outcomes among premature infants exposed to predominately MOM versus DHM. Methods/Search Strategy: Databases including PubMed, CINAHL and Cochrane were searched (2020-2021) using the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analysis) guidelines. Evidence was classified using the John Hopkins evidence-based practice levels and quality of evidence. Results: Eleven studies met inclusion criteria. Studied neonatal outcomes included ( a ) growth parameters (n = 8), ( b ) neonatal morbidities (n = 6), and ( c ) gut microbiome (n = 4). Overall, evidence suggests DHM exposure is beneficial but not equivalent to MOM feeding. Compared with DHM, greater doses of MOM are ideal to enhance protection primarily related to infant growth, as well as gut microbiome diversity and richness. Implications for Practice: Standardized and evidence-based practices are needed to clearly delineate optimal use of DHM without undermining maternal and neonatal staff efforts to support and promote provision of MOM. Implications for Research: Additional evidence from high-quality studies should further examine differences in neonatal outcomes among infants exposed to predominately MOM or DHM in settings using standardized and evidence-based feeding practices.